Detection of polarons in reduced vanadium oxide V2O(5-delta) (2022)
This project studied the change in magnetization of nanoparticles of pentoxide vanadium when subjected to controlled annealing. This study focuses on the induction of a stable net magnetic moment on the compound for applications such as spintronics and morphological computation. In addition, the study of the physical explanation of the change in magnetization is focused on the presence of polarons. These polarons in the sample were detected using a superconductor magnet. The project also includes studies of Raman spectroscopy, relaxation times, magnetization, and analysis of the presence of polarons on the crystal lattice.